Modeling the interaction of IEEE 802.3x hop-by-hop flow control and TCP end-to-end flow control - Malhotra, R.; van Haalen, R.; Mandjes, M.; Nunez-Queija, R. (2005 Next Generation Internet Networks, 2005)
Ethernet is rapidly expanding beyond its niche of local area networks. However, its success in larger metropolitan area networks will be determined by its ability to combine simplicity, low costs and quality of service. A key element in successfully transporting bursty traffic and at the same time providing QoS, is congestion control. The Ethernet standard IEEE 802.3x defines a hop-by-hop congestion control mechanism. The performance of this scheme generally depends on its interaction with higher layer application traffic, and especially, with TCP controlled traffic which has its own end-to-end congestion control mechanism. In this paper we focus on the performance modeling and analysis of this interaction. Our model takes into account the influence of various network and traffic parameters. The validity of the proposed model is assessed by comparison of the results to simulations. In our experiments we observe that an increase of the round trip time has a positive influence on the interaction of hop-by-hop and TCP congestion control, and that the use of hop-by-hop flow control is only beneficial when the load is not high.